A Case of Giant Hydronephrosis Hidden by Obesity in an 11-year-old Boy - Gumbich Hwang; Inchan Hwang; Seol Ho Choo; Hyun Gi Kim; Ki Soo Pai (Korean Society of Pediatric Nephrology, 2017)
Giant hydronephrosis (GH) is a rare urological entity and usually presents with more than a liter of fluid in the collecting system. It may mimic a progressive and benign abdominal cystic tumor. We report a case of GH in an 11-year-old obese boy who presented with abdominal distension and dyspnea on exercise. Hydronephrosis was caused by ureteropelvic junction obstruction, with 2,300 mL of fluid in the collecting system. Diagnostic and therapeutic features of this case are discussed, with reference to current literature.